Transformasi Digital Dalam Pendidikan Tinggi: Peran Pelatihan Digital Dalam Meningkatkan Kompetensi Dan Kinerja Tenaga Kependidikan: - Muhammad Sarifudin; Siti Maria; Dwi Martiyanti; Irsan Tricahyadinata (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
Digital transformation in higher education requires administrative staff to have sufficient digital competence to enhance efficiency, productivity, and service quality. This study examines the effect of digital training on staff performance, both directly and through digital competence as a mediating variable. A quantitative method was employed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). Results indicate that digital training positively and significantly affects staff performance. Digital competence also mediates the relationship between digital training and performance. The outer model confirms all indicators are valid and reliable, while the inner model shows strong variable relationships. These findings support previous research on the importance of digital competence in improving performance. The study emphasizes the need for continuous, needs-based digital training to support digital transformation and strengthen the effectiveness and competitiveness of administrative staff in higher education.